Desenvolvimento de sistema auxiliar de resfriamento evaporativo, para arrefecimento de transformadores de força - Araújo, Ismael Nickson Pinto de (2016)
The consumption of electricity in our social environment such as in houses, apartments, business, industries, hospitals, it’s achieved thanks to an equipment that makes the levels of tension and electric current acceptable as demanded by the standards, so we can benefit from electricity in a safe and efficient way, these equipment are the power transformers. Due your relevance, techniques that retard or avoid the failures in these equipment, aiming a better availability and a smaller number of maintenance stops, are the theme of several researchers and studies centers. A very common failure in medium and large transformers that are used in transmission and distribution of power, is the degradation of the insulating function of transformer's core that it is caused mainly by the adverse gradient of temperature that circulates in the core through the insulating oil. The present work analyzes the efficiency of a transformer's cooling auxiliary system, that aims dissipate the heat absorbed by the oil in a quick and efficient way, decreasing the degradation of the insulating function and increasing its lifespan. The system consist of water spray nozzles, that it will be installed in the transformer’s radiator, in front of the fans, in the same direction of the air flow. The water spraying in the air flow, will cause a temperature decrease and a humidity increase, due to a phenomenon known as evaporative cooling, where heat from the air makes the small drops of water evaporate quickly. It will be analyzed the water flow rate in the spraying, the amount and placement of the water spray nozzles through the radiator and the air flow of the fans. So the system has thermal and energetic efficiency. Will be used a control system that includes a variable-frequency drive (VFD), temperature sensors and a data acquisition board (DAQ), all monitored through LabVIEW.